Vectors of virus and mycoplasma diseases: an overview - Thottappilly, G.; Rossel, H.W.; Reddy, D.V.R.; Morales, F.J.; Green, S.K.; Makkouk, K.M. (1990)
Many virus diseases of plants and probably all diseases caused by mycoplasma-like organisms (MLOs) are transmitted by insect vectors. In this review the vector insect groups of viruses and MLOs on tropical food legumes are discussed. An overview is given quoting examples of the relations between the vector and the virus or MLO.